Untethered near‐field drone‐based antenna measurement system for microwave frequencies using multiple reference antennas for phase and drone location recovery. Issue 13 (8th September 2022) - Parini, Clive G.; Gregson, Stuart F.; Brown, Anthony K.
Abstract: The simulation of a novel drone‐based near‐field (NF)/far‐field (FF) antenna measurement system enabling the reconstruction of Antenna Under Test (AUT) phase and the true location of the untethered drone using multiple land‐based reference antennas is described. The mathematical approach follows the principle used within Global Positioning System (GPS) position and time recovery. Conceptually, the satellites are replaced by ground‐based reference antennas of known location, the user location is now the drone location and the user clock offset is replaced by the unknown AUT phase radiated at the angle subtended between the AUT and drone location. This addresses the need for drone‐based NF/FF antenna measurement of large in situ VHF/UHF antenna arrays plus the need to measure the installed performance of microwave antennas on structures such as buildings, aircraft and ships. To assess the viability, a computer simulation of the measurement system is constructed and its performance is analysed in terms of the accuracy of reconstruction of the AUT phase and true drone location, as well as the NF/FF radiation pattern accuracy in terms of the equivalent multipath level (EMPL). An example measurement 'range', comprising AUT location and six fixed reference antennas, demonstrates a wide AUT operating bandwidth of (0.5–2) GHz, with EMPL < −50 dB over the forward hemisphere.